The realization of the mission of the Church in associations connected with the spirituality of the Society of St. Francis de Sales - DOMASZK, ARKADIUSZ (Prawo Kanoniczne, 2012)
Polish legislation respects the law to associate. Among numerous different Polish associations there are also those, which are connected with spirituality and aims of specific religious institutes. One can find, inter alia, the associations relating to Salesian charism. This research paper refers to associations, which exist in Poland, and are connected with spirituality of the Society of St. Francis de Sales. The research is focused on the issue of how the activity of some selected associations refers to the realization of the Society of St. Francis de Sales’s aims, and at the same time to the mission of the whole Church. To outline the whole context of existence of associations, in the initial points of this paper, there have been shown the Polish Law, Canon Law, and also the Society of St. Francis de Sales’s Own Law. The following associations were the subject of study: Salesian Organisation of Youth Education, Salesian Movement of Concern for the Youth “Saltrom”, Salesian Sport Organization of the Republic of Poland SALOS. Salesians cooperate with various groups of the faithful, also with the youth mission oriented associations, and with those, which don’t have the canonical nature of the faithful associations, but have a civil legal personality. What is important is that those associations take up educational and evangelisation activity of children and youth. In this way they are closely related with the principal mission of the Society of St. Francis de Sales. Also significant is the fact that presented associations apply Salesian educational system, also known as preventive, in statutory stipulations, as well as in practice. Furthermore, the introduced associations carry out the stipulations of integral development of children and youth, which is one of the stipulations of the Church mission in the scope of Catholic education. The existence of associations that refer to the spirituality of certain religious institute constitute the immense potential useful to people and their development. The members of the associations show a great commitment, which is a very positive social experience. To preserve the spiritual wealth, in this case the Salesian one, it is vital to give an attention on both the institute and the association side. In addition, the existence of such specific association subgroup is an interesting matter to further research in the context of Law of Associations.